1990
DOI: 10.1093/protein/4.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the C-terminal amino acid to the stability of Bacillus subtilis neutral protease

Abstract: The role of the C-terminal Leu300 in maintaining thermal stability of the neutral protease of Bacillus subtilis was investigated. From model building studies based on the three-dimensional structure of thermolysin, the neutral protease of B. thermoproteolyticus, it was concluded that this residue is located in a hydrophobic pocket composed of residues located in the C-terminal and the middle domain. To test the hypothesis that Leu300, by contributing to a stabilizing interaction between these domains, is impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 20 publications
(26 reference statements)
0
28
0
Order By: Relevance
“…5; Table 3 Examination of the three residues in a three-dimensional model of the B. stearothermophilus Npr, constructed on the basis of the well-defined thermolysin structure (6), showed that residues 4, 59, and 66 are located at the surface of the protein (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…5; Table 3 Examination of the three residues in a three-dimensional model of the B. stearothermophilus Npr, constructed on the basis of the well-defined thermolysin structure (6), showed that residues 4, 59, and 66 are located at the surface of the protein (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular Biology-The nprT gene encoding the TLP of B. stearothermophilus CU21 (25) (TLP-ste) was cloned, subcloned, and expressed as described previously (26). Site-directed mutagenesis was performed on subcloned fragments of the TLP-ste gene using the QuikChange site-directed mutagenesis kit from Stratagene, La Jolla, CA.…”
Section: Modeling and Mutantmentioning
confidence: 99%
“…Site-directed mutagenesis was performed on subcloned fragments of the TLP-ste gene using the QuikChange site-directed mutagenesis kit from Stratagene, La Jolla, CA. The nucleotide sequences of mutated fragments of the nprT gene were verified by DNA sequencing and the mutated fragments were subsequently cloned into variants of the Bacillus expression vector pGE501 (26) containing the TLP-ste gene with a deletion of the previously subcloned fragment.…”
Section: Modeling and Mutantmentioning
confidence: 99%
“…The protease-deficient strain Bacillus subtilis DB117 43 was used as host for this plasmid, and its variants were obtained by site-directed mutagenesis. Cells harboring these plasmids were grown at 37°C in TY broth containing 5 g/ml chloramphenicol as antibiotic.…”
Section: Reagents-14-dithio-dl-threitol (Dtt) and N-(3-[2-furyl]acrymentioning
confidence: 99%
“…Expression and Purification of Wild Type and Mutant EnzymesWild type and mutant proteins were produced and purified as described previously (43,48) using affinity chromatography on Bacitracin-silica. The enzymes were stored in elution buffer containing 20 mM sodium acetate, pH 5.3, 5 mM CaCl 2 , 2.5 M NaCl, 20% (v/v) isopropanol, and 0.03% (w/v) sodium azide.…”
Section: Reagents-14-dithio-dl-threitol (Dtt) and N-(3-[2-furyl]acrymentioning
confidence: 99%